High temperatures alter physiological properties of pyramidal cells and inhibitory interneurons in hippocampus - Kim, Jennifer; Connors, Barry (Frontiers in Cellular Neuroscience, 2012)
Temperature has multiple effects on neurons, yet little is known about the effects of high temperature on the physiology of mammalian central neurons. Hyperthermia can influence behavior and cause febrile seizures. We studied the effects of acute hyperthermia on the immature hippocampus in vitro by recording from pyramidal neurons and inhibitory oriens-lacunosum moleculare (O-LM) interneurons (identified by green fluorescent protein expression in the GIN mouse line). Warming to 41°C caused depolarization, spontaneous action potentials, reduced input resistance and membrane time constant, and increased spontaneous synaptic activity of most pyramidal cells and O-LM interneurons. Pyramidal neurons of area CA3 were more strongly excited by hyperthermia than those of area CA1. About 90% of O-LM interneurons in both CA1 and CA3 increased their firing rates at hyperthermic temperatures; interneurons in CA3 fired faster than those in CA1 on average. Blockade of fast synaptic transmission did not abolish the effect of hyperthermia on neuronal excitability. Our results suggest that hyperthermia increases hippocampal excitability, particularly in seizure-prone area CA3, by altering the intrinsic membrane properties of pyramidal cells and interneurons.